COVID-19 and CKD: Employment, Food Security and Healthcare in El Salvador. Issue 1 (9th November 2022) - Leibler, Jessica H.; Keogh, Sinead A.; Jarquín, Emmanuel; Garcia-Trabanino, Ramon; Velázquez, Juan José Amador; Pilarte, Damaris Lopez; Beltran, Marvin; Delgado, Iris S.; Petropoulos, Zoe E.; Friedman, David J.; Brooks, Daniel R.; Scammell, Madeleine K.
Background: In Central America, the COVID-19 pandemic coexists with a devastating epidemic of chronic kidney disease of unknown origin. The consequences of these overlapping health crises remain largely unknown. Methods: We assessed vulnerability to and impact of the first wave of COVID-19 on participants in a cohort study of chronic kidney disease (CKD) in El Salvador (n = 229). Participants were contacted by phone during August and September 2020. We queried changes to employment, healthcare access, household income and food security due to the pandemic (from March 2020 until the time of the interview) and COVID-19-associated symptoms during that time. Findings: We reached 94% of the cohort (n = 215). Nearly 40% of participants reported an unexpected change in employment or work activities and 8.8% reported new unemployment due to the pandemic. Participants with CKD (n = 27) had higher odds of reporting new income insecurity, food insecurity, and reductions in medical care access due to the pandemic. COVID-19-associated symptoms (an approximation of disease) were reported in 7.0% (n = 15). Participants with CKD were more likely to report COVID-19-associated symptoms compared to those without CKD, although these differences were not statistically significant. Conclusions: Overall, participants with CKD suffered greater economic consequences as a result of the pandemic and may have experienced higher incidence of COVID-19 disease, although laboratory diagnostics would be required to draw this conclusion. Longitudinal analyses are required to comprehensively evaluate the implications of the pandemic for individuals with CKD in Central America.